2019
DOI: 10.1186/s12871-019-0741-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of general anesthesia versus conscious sedation for Stroke undergoing endovascular treatment: a meta-analysis

Abstract: Background The impact of anesthesia strategy on the outcomes of acute ischemic stroke (AIS) patients undergoing endovascular treatment is currently controversy. Thus, we performed this meta-analysis to compare the differences of clinical and angiographic outcomes between general anesthesia (GA) and conscious sedation (CS). Methods A literature search in PubMed, Embase, and Web of Knowledge databases through February 2019 was conducted for related records on GA and CS of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In this study, general anesthesia was associated with a higher reperfusion rate when compared to conscious sedation. This finding has been previously described in a RCT [ 27 ]; however, a large systematic review and meta-analysis of 6703 patients did not find a difference between anesthesia type and rates of sufficient reperfusion [ 28 ]. This interesting aspect should be further explored in future trials, since the decision for or against general anesthesia is frequently encountered in daily practice [ 29 ].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, general anesthesia was associated with a higher reperfusion rate when compared to conscious sedation. This finding has been previously described in a RCT [ 27 ]; however, a large systematic review and meta-analysis of 6703 patients did not find a difference between anesthesia type and rates of sufficient reperfusion [ 28 ]. This interesting aspect should be further explored in future trials, since the decision for or against general anesthesia is frequently encountered in daily practice [ 29 ].…”
Section: Discussionsupporting
confidence: 80%
“…Multiple non-randomized and a few randomized studies have examined different options, including conscious sedation or general anesthesia. In general, non-randomized studies have found that general anesthesia leads to worse functional outcome and a higher mortality rate,787980818283 but some randomized, single center trials including AnStroke,84 SIESTA,85 and GOLIATH,86 showed no difference in mortality for general anesthesia versus conscious sedation, with better functional outcomes for general anesthesia in SIESTA but no difference in AnStroke or GOLIATH.…”
Section: Mechanical Thrombectomy For Acute Ischemic Strokementioning
confidence: 99%
“…Former meta-analyses suggested that general anesthesia compared to conscious sedation for endovascular therapy decreases recovery and increases death and disability. (Abou-Chebl et al, 2010;Brinjikji et al, 2015;Wan et al, 2019) The link of general anes- F I G U R E 3 Forest plot of the general anesthesia versus conscious sedation during the endovascular therapy for acute ischemic stroke related to successful recanalization at 24 hr F I G U R E 4 Forest plot of the general anesthesia versus conscious sedation during the endovascular therapy for acute ischemic stroke related to mortality at 90 days F I G U R E 5 Forest plot of the general anesthesia versus conscious sedation during the endovascular therapy for acute ischemic stroke related to interventional complication Mundiyanapurath et al, 2015) may be clarified by blood pressure reductions and an extended delay of time to groin puncture in the general anesthesia group, both of which have been related to inferior endovascular therapy results. (Davis et al, 2012) Opposite to many nonrandomized studies and former meta-analyses, this study appears to support the idea that endovascular therapy may be performed with both conscious sedation and general anesthesia with favoring general anesthesia due to its relatively lower symptomatic intracranial hemorrhage result (p = .05).…”
Section: Discussionmentioning
confidence: 99%
“…Former systematic review and meta-analyses (Abou-Chebl et al, 2010;Brinjikji et al, 2015;Wan et al, 2019) and observational studies (Abou-Chebl et al, 2010Just et al, 2016;Mundiyanapurath et al, 2015) showed worse results from general anesthesia compared with conscious sedation in endovascular therapy.…”
Section: Introductionmentioning
confidence: 99%